Mathematical analysis for business and economics - Schelin, Charles W.; Bange, David W. (The Prindle, Weber & Schmidt series in mathematics, 1988)
Shows signs of wear. Loose Binding, some writing. Eligible for FREE Super Saving Shipping! Fast Amazon shipping plus a hassle free return policy mean your satisfaction is guaranteed! Tracking number provided with every order.